Dynamics of Gay Men’s Organized Social Life on Dating Apps - Saraiva, Luiz Alex Silva (Organizações & Sociedade, 2023)
The forms technology has assumed in contemporaneity are as varied as they are ubiquitous. They have transformed the ways of living in society in a context of increasing mediation of social relations by technology, which seems to complement face-to-face interactions by establishing new social existence modalities. This article aims to discuss the dynamics of social life organized on dating apps around four basic axes: virtuality, sociability, stereotyping, and violence. The study is based on an inductively inspired survey of users of the Grindr app in Belo Horizonte, Minas Gerais, Brazil. The data suggest that virtuality implies superficiality and a disposable attitude to relationships, which lead to a form of ephemeral sociability in which stereotyping is ostensibly employed to accelerate the dynamic by attributing preconceptions to other users. Indeed, these aspects are materialized as varied and systematic violence practices, which are frequent in the context of the investigated application. The main conclusions reveal that organized social life humanizes organizational analysis and advances the concept of organization by humanizing the process and including the ways of organizing practiced by social groups. This includes situating the researcher in a process that implicates them and politicizes knowledge production.